Two new tanshinone derivatives from the rhizomes of Salvia miltiorrhiza and their antiviral activities. Issue 1 (2nd January 2020) - Yin, Zhao-Kun; Feng, Zi-Ming; Jiang, Jian-Shuang; Zhang, Xu; Zhang, Pei-Cheng; Yang, Ya-Nan
Abstract: Two new naturally occurring products named salviamine G (1) and 4-methyl-9-(ethoxycarbonyl)-8-naphthoic acid (2) were isolated from the rhizomes of Salvia miltiorrhiza . Their structures were elucidated using spectroscopic data (UV, IR, HRESIMS, 1D and 2D NMR). Compounds 1 and 2 were screened for their inhibitory activity against HSV-1 and influenza A (H3N2) using acyclovir (ACV, IC50 = 0.67 μ M) and oseltamivir (IC50 = 2.01 μ M) as a positive control. Compound 1 exhibited moderate inhibitory activity against HSV-1 and influenza A (H3N2) with IC50 values of 11.11 and 8.62 μ M, respectively. Graphical Abstract: